Moral Economies and Codes of Conduct: the Social Organization of Canadian Experimental Psychology - Schoenherr, Jordan (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2019)
Psychological science has flourished in North America since the late 19th century. As laboratories multiplied, professional organizations began to emerge to facilitate communications through journals and conferences. This article examines the development of the moral economy of professional and scientific psychology in Canada. While the general features of the social organization of psychological science in Canada and the United States have followed similar trajectories, important differences are also evident. In particular, these differences are apparent in the values and conventions outlined by the two largest professional organizations in Canada (CPA) and the United States (APA).